Politik Hukum Judicial Review Ketetapan MPR - Anshori, Lutfil (al-Daulah: Jurnal Hukum dan Perundangan Islam, 2016)
Abstract: recent development in Indonesian constitutional law in the field of legislation indicates a legal vacuum in the review system of legislation, namely the judicial review of TAP MPR (decree of People Consultative Assembly, the highest political entity in Indonesia). Judicial review is a mechanism of legal control by the judiciary against the laws made by the legislative or executive. The principle is the implementation of the rule of law and separation of power system which is embraced by UUD 1945. The article argues the need to consider legal and political in resolving judicial review problems of TAP MPR to avoid infringement of the constitutional rights of citizens. In the legal political perspective it can be concluded that the judicial review of TAP MPR can be done by Mahkamah Konstitusi (Constitutional Court) based on amendment of the constitutional (UUD 1945) that locate the basic function of Mahkamah Konstitusi as the guardian of the constitution. The Mahkamah must take a role to fill the legal vacuum in the judicial review of TAP MPR.Keywords: Judicial Review, TAP MPR, the legislation.Â Abstrak: Perkembangan ketatanegaraan Indonesia dewasa ini dalam ranah peraturan perundang-undangan menunjukkan adanya kekosongan hukum di dalam sistem pengujian peraturan perundang-undangan, yakni judicial review TAP MPR. Judicial review merupakan mekanisme kontrol hukum oleh lembaga yudisial terhadap peraturan perundang-undangan yang dibuat oleh lembaga legislatif maupun eksekutif. Prinsip ini merupakan implementasi dari prinsip negara hukum dan sistem pemisahan kekuasaan (separation of power) yang dianut oleh UUD 1945. Perlu ada pertimbangan politik hukum dalam menyelesaikan masalah pengujian TAP MPR ini, agar di kemudian hari tidak merugikan hak-hak konstitusional warga negara.Â  Dalam prespektif politik hukum, judicial review TAP MPR dapat dilakukan oleh Mahkamah Konstitusi dengan mendasarkan pada perubahan kondisi ketatanegaraan pasca amandemen UUD 1945 serta fungsi dasar Mahkamah Konstitusi sebagai pengawal konstitusi. Mahkamah Konstitusi sebagai lembaga pengawal konstitusi harus berani mengambil peran untuk mengisi kekosongan hukum dalam pengujian TAP MPR.Kata Kunci: judicial review, TAP MPR, peraturan perundang-undangan.